2014
DOI: 10.1523/jneurosci.2736-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Enhances Excitability of Medial Habenular Neurons via Facilitation of Neurokinin Signaling

Abstract: The medial habenula (MHb) densely expresses nicotinic acetylcholine receptors (nAChRs) and participates in nicotine-related behaviors such as nicotine withdrawal and regulating nicotine intake. Although specific nAChR subunits are identified as being involved in withdrawal behavior, the cellular mechanisms through which nicotine acts to cause this aversive experience is unclear. Here, we demonstrate an interaction between the nicotinic and neurokinin signaling systems that may form the basis for some symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 69 publications
0
52
0
Order By: Relevance
“…This is particularly important given that our pharmacological experiments suggest that nAChRs containing a6 subunits are a minority, although of high sensitivity, subtype in MHbVI. These results demonstrate the importance of considering MHb subregions independently when studying nAChRs and chronic nicotine, as several recent studies did not identify changes in the response of MHb neurons to nicotine when the MHb was analyzed without considering subregions (Gorlich et al, 2013;Hsu et al, 2013;Dao et al, 2014).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This is particularly important given that our pharmacological experiments suggest that nAChRs containing a6 subunits are a minority, although of high sensitivity, subtype in MHbVI. These results demonstrate the importance of considering MHb subregions independently when studying nAChRs and chronic nicotine, as several recent studies did not identify changes in the response of MHb neurons to nicotine when the MHb was analyzed without considering subregions (Gorlich et al, 2013;Hsu et al, 2013;Dao et al, 2014).…”
Section: Discussionmentioning
confidence: 59%
“…MHb neurons fire spontaneous action potentials in slice preparation (Gorlich et al, 2013;Dao et al, 2014;Shih et al, 2014). To examine the effects of short-term nicotine exposure on MHbVL and MHbVI neuron firing rates, we recorded baseline and nicotine-elicited action potential firing.…”
Section: Resultsmentioning
confidence: 99%
“…Lentivirus-mediated gene delivery to the MHb restored β4 nAChR subunit expression on a β4KO background, forming putative a3β4* nAChRs in MHb soma and terminals innervating the IPN. MHb β4* nAChRs are required for nicotine-evoked excitatory responses (Dao et al, 2014;Görlich et al, 2013;Hsu et al, 2013), and β4* nAChRs on MHb terminals are required for nicotine-evoked acetylcholine release (Beiranvand et al, 2014;Grady et al, 2009). We found that partial re-expression of β4* nAChRs along the length of MHb neurons (mean: 26.0%) did not rescue nicotine IVSA.…”
Section: Discussionmentioning
confidence: 72%
“…Fowler et al (2011) have shown that habenular nAChRs containing the a5 subunit regulate the consumption of nicotine at normally aversive high doses. Dao et al (2014) used patch-clamp electrophysiology in mouse brain slices to show that acute nicotine administration increases the intrinsic excitability of MHb neurons, and that this increase is due to the presence of a5b2*-containing receptors. By activating a5* receptors, acute nicotine exposure facilitates the release of neurokinins on MHb neurons expressing neurokinin receptors type 1 and 3, whose activation increases intrinsic MHb neuron excitability whereas chronic nicotine exposure reduces the responsiveness of a5* nAChRs and the neuromodulatory effect of nicotine on intrinsic excitability probably as a result of nAChR desensitisation, and this may contribute to aversive experiences during nicotine withdrawal.…”
Section: Recent Electrophysiological and Pharmacological Studies Havementioning
confidence: 99%